Conflicting Opinions and Emotions in Students’ Responses to Feminist Resistance in the Film Photocopier - Artanti Puspita Sari (IJLECR (International Journal of Language Education and Cultural Review), 2023)
The film Photocopier depicts how its main character, a victim of sexual harassment, exercised her feminist resistance toward hegemonic and patriarchal power in society. Studies have been conducted in the past to examine feminist resistance in this film and a few other films. Yet, none have looked closely into students' responses to feminist resistance in those films. Engaging students in responding to film contents is important because films have the potential to provoke students’ critical thinking and emotions toward various issues in society, such as issues related to the victimization of women. To address the gap in research, this   study aimed to examine how students express their opinions and emotions toward the female main character’s resistance in the film Photocopier. It also aimed to analyze how those opinions and emotions may influence students’ potential actions when faced with sexual harassment issues in real life. Using an audience response method, data were collected through observations that included film viewing, a classroom discussion, and an open-ended questionnaire. The study involved eleven female and two male graduate students in a literature teaching and appreciation course. The results showed that each student experienced conflicting opinions and emotions with regard to the main character’s resistance. After watching the film, students felt motivated and inspired to advocate for victims of sexual harassment in real life. The researcher argues that conflicting opinions and emotions were inevitable consequences of students’ critical thinking and emotional processes while responding to the film. The negative opinions and emotions that even led to victim blaming did not hinder them from supporting the main character’s efforts to obtain justice. Furthermore, the researcher argues for the necessity of developing audience responses to films as a powerful strategy in critical literature pedagogy.